2019
DOI: 10.1371/journal.pone.0222337
|View full text |Cite
|
Sign up to set email alerts
|

Pontoscolex corethrurus: A homeless invasive tropical earthworm?

Abstract: The presence of earthworm species in crop fields is as old as agriculture itself. The earthworms Pontoscolex corethrurus (invasive) and Balanteodrilus pearsei (native) are associated with the emergence of agriculture and sedentism in the region Amazon and Maya, respectively. Both species have shifted their preference from their natural habitat to the cropland niche. They contrast in terms of intensification of agricultural land use (anthropic impact to the symbiotic soil microbiome). P. corethrurus inhabits co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 73 publications
0
1
0
Order By: Relevance
“…Some farmers stated that earthworms caused the soil to become dense and decreased. A similar effect has elsewhere been attributed specifically to Pontoscolex corethrurus as an invasive earthworm linked to agricultural expansion (Ortíz-Ceballos et al 2019). Although the name P. corethrurus might in fact relate to a morphospecies with multiple taxonomic identities, there is no consensus on its preferred food source (Taheri et al 2018) with a 100% litter reported to be lethal, and a preference rhizosphere carbon sources indicated.…”
Section: Castmentioning
confidence: 79%
“…Some farmers stated that earthworms caused the soil to become dense and decreased. A similar effect has elsewhere been attributed specifically to Pontoscolex corethrurus as an invasive earthworm linked to agricultural expansion (Ortíz-Ceballos et al 2019). Although the name P. corethrurus might in fact relate to a morphospecies with multiple taxonomic identities, there is no consensus on its preferred food source (Taheri et al 2018) with a 100% litter reported to be lethal, and a preference rhizosphere carbon sources indicated.…”
Section: Castmentioning
confidence: 79%